Manfaat dan Pengembangan Teknologi Umbi Porang (Amorphophallus muelleri Blume) melalui Metode Pengeringan - Serapin Putri, Putu Ayu Viona (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2022)
Porang tubers are one of the most popular plant cultivations in the international market. The benefits and advantages of porang tuber cultivation make porang tubers one of the strengths to be able to reduce imports. The benefits of this cultivation will certainly be felt by farmers. Because of the great benefits felt, it would be very appropriate if porang tubers would be strongly associated with technology, especially in the drying method. This study aims to be able to show descriptively the method of drying porang tubers from conventional things that still depend on solar heat to technology-based to the creation of a drying machine. The application of technology will certainly facilitate the community in accelerating the production of porang tubers. Optimization to achieve time efficiency is certainly the biggest advantage. Until finally the factors inhibiting production will be minimized. Key note: Porang tubers, drying machine, solar heat